FACTORS OF ORGANIZATIONAL CULTURE RELATED TO ORGANIZATIONAL EFFECTIVENESS IN THE SATKES KODIKLATAL - Mega Nurmalasari Wira Putri; Djazuly Chalidyanto (JOURNAL ASRO, 2020)
Organizations exist because of human needs through relationships, interactions, communications, socialization to one another to meet common goals. Organizational culture becomes an important part of this influence on organizational effectiveness (a term for the fulfillment of organizational goals). This study aims to determine how the organizational culture conditions of the Kodiklatal Health Unit by using indicators according to the Denison organizational culture model, namely involvement, consistency, adaptability and mission. In addition, a theoretical study on the importance of organizational culture from the background for this research is because the Kodiklatal Satkes is a work unit under the Kodiklatal, which has duties other than carrying out health services for all military and civil servants who serve in Kodiklatal, all students who are carrying out education at Kodiklatal and Family members of military and civil servants Kodiklatal, also carry out health support for every military activity / training carried out by students and members of the Kodiklatal military. The research method is a quantitative method by collecting data using a questionnaire with a sample population of 50 employees of the Kodiklatal Health Unit, processed using descriptive statistics. The results showed that the average overall organizational culture was in the very weak category with the strongest score on the mission sub-variable and the weakest on the involvement sub-variable. Keywords: Culture, Organization, and Denison